Ethnic variations in mental health among 10–15-year-olds living in England and Wales: The impact of neighbourhood characteristics and parental behaviour. (May 2018) - Jonsson, Kenisha Russell; Vartanova, Irina; Södergren, Marita
Abstract: Several studies indicate that young people from certain ethnic minority groups in Britain have significant mental health advantages over their White majority counterparts, but the reasons for these differences have not been adequately explored. This work analyses the impact of neighbourhood characteristics, measured by socioeconomic deprivation; crime; living conditions; ethnic density and parenting behaviour on the mental health of young people. To determine the impact of these factors on mental health among young people, geocoded data from waves 1, 3 and 5 of the UK Household Longitudinal Study ( UKHLS ) are merged with small area statistics from the 2011 census, and multilevel linear regression models are fitted to the sample of 5513 (7302 observations) 10–15-year-olds of varying ethnicity residing in England and Wales. We find that mental health is generally poorer for White British youths, even after accounting for individual/family-level predictors, neighbourhood characteristics and parental behaviour than it is for minority youths. In keeping with results from studies of adult populations, neighbourhoods with high levels of deprivation are associated with poorer mental health. However, some aspects of parenting behaviour appear to have a more significant impact on the mental health of young people from ethnic minority backgrounds than on White British youths. Further research into factors that influence inter-ethnic disparities in mental health among young people is warranted, given that clear differences remain after the models in this study are fully adjusted. Highlights: Neighbourhood characteristics are associated with young people's mental health. Most of the variability in mental health is due to individual-level variation. Adjustment for parenting increased the minority/White British mental health gap. Deprivation associated more negatively with mental health in White British youths. The proportion of co-ethnic residents was not associated with youth mental health.